The effect of dual fuel producer gases with Y-shaped mixing chamber on single cylinder spark ignition engine operation / Mohd Mahadzir Mohammud@Mahmood ... [et al.] - Mohammud@Mahmood, Mohd Mahadzir; Mohd Fauzi, Ahmad Faiz; Ismail, Noor Iswadi; Mahamad Basri, Mahamad Hisyam; Mohamad, Shamsul (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
In the operation of SI engines, alternative biomass fuels such as rice husk can be utilized. This will contribute limit the consumption of fossil fuels. The dual-fuel approach can also be employed on SI engines. One of the solutions that can be employed in dual-fuel SI engines with gasoline is producer gas, a flammable gas created by biomass gasification. However, the numerous methods of incorporating gases into SI engines necessitate substantial investigation. In this study, producer gas and gasoline are combined and fed into an SI engine. The dual fuel is used to power the single-cylinder SI engine. The most optimal operation of the Y-shaped mixing chamber is investigated. Experiments were conducted to determine the optimal air-producer gas ratio values based on the SI engine's ability to operate in time at idle. Two variables were chosen as inputs: air producer gas ratio and fuel mixture percentage. According to the study's findings, an air-producer-gas ratio of 1.5:1 with 50% gasoline results in better mixing. The single-cylinder SI engine has been running smoothly and longer than other parameters without knocking.